Grunting in tennis increases ball velocity but not oxygen cost - Callison, E. R.; Berg, K. E.; Slivka, D. R. (The Journal of Strength and Conditioning Research, 2014)
Grunting is widely used by professional tennis players, but no research has been done to verify enhanced performance with grunting. Therefore, the purpose of this study was to determine if grunting enhanced ball velocity in groundstrokes and secondly, to determine if grunting increased the physiological cost of hitting (VO2, HR, VE/VO2, and RPE). Participants were 10 members of the men's (n = 5) and women's (n = 5) tennis teams at a Division I university who had just completed their indoor competitive season. Two hitting sessions were used as players repetitively hit forehand and backhand shots while either grunting or not grunting. Each hitting session consisted of five 2-minute periods with a 1-minute break in between each period. Ball velocity was measured with a radar gun. During each hitting session, players wore a portable metabolic measuring unit. HR was monitored using a Polar monitor, and RPE was assessed using Borg's 6-20 scale. Grunting increased ball velocity (kph) 3.8% compared with non-grunting condition (p < 0.034) with the mean ± SD being 83.4 ± 0.6.1 and 80.3 ± 0.8.7, respectively. The physiological responses (VO2, HR, VE/VO2, and RPE) for the 2 hitting conditions were not significantly different for any variable. When averaged across both hitting conditions, HR over the 5-time periods was higher in periods 3-5 than period (p < 0.018) 1, whereas VE/VO2 and RPE were greater in periods 2-5 than period 1 (p = 0.001). RPE significantly increased over time with periods 2-5 being greater than period 1 (p = 0.001). It was concluded that grunting increased ball velocity without increasing VO2 or VE/VO2 or RPE in comparison with not grunting. It may be worthwhile for players and coaches in tennis and other sports to experiment with grunting to determine possible improvement in performance.